Bias Status Quo dan Pencatatan Akuntansi : Studi Exploratif - Nariswari Warashinta; Supramono Supramono (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2022)
This study aims to analyze the status quo bias as the reason MSME owners do not make accounting records. Exploratory Study was used in this study and data were obtained through interviews with five MSME owners in Salatiga City who are engaged in grocery and culinary businesses and they do not make accounting records. The results of the study indicates that there is a tendency for MSME owners to experience a status quo bias so that they do not make accounting records. This is because they feel comfortable, ignore the opportunity for accounting profits, stop at their desire and they feel worried about the risks that will be faced if they make accounting recods. Another finding is that the status quo bias is not permanent or dynamic,, so that if MSME owners are given certain treatment, they are likely to be willing to make accounting records